1976
DOI: 10.1136/gut.17.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum gastrin response to lower oesophageal sphincter pressure.

Abstract: Exogenous gastrin is a powerful stimulant of lower oesophageal sphincter (LES) contraction (Giles et al., 1969). Castell and Harris (1970) proposed that endogenous gastrin is a major controller of basal lower oesophageal sphincter pressure (LESP) on the basis of observed LESP changes with alteration of intragastric pH. Changes in circulating gastrin with pH manipulation were assumed in this study, as they were with protein feeding experiments in man in which a rise in LESP occurred after feeding (Nebel and Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Nevertheless, changes 102 secondary effects on gastrin release, and gastrin concentrations were measured during cimetidine infusion in the present studies. The role of gastrin as a physiological determinant of LOS pressure is now in debate, and the recent studies of Dent and Hansky (1976) and our own unpublished data, have failed to confirm earlier suggestions that gastrin is involved in LOS control (Giles et al, 1969;Castell and Harris, 1970;McCall et al, 1975). In any event, mean serum gastrin concentrations did not show any statistically significant variation from basal values (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, changes 102 secondary effects on gastrin release, and gastrin concentrations were measured during cimetidine infusion in the present studies. The role of gastrin as a physiological determinant of LOS pressure is now in debate, and the recent studies of Dent and Hansky (1976) and our own unpublished data, have failed to confirm earlier suggestions that gastrin is involved in LOS control (Giles et al, 1969;Castell and Harris, 1970;McCall et al, 1975). In any event, mean serum gastrin concentrations did not show any statistically significant variation from basal values (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, many of the studies reporting a rise in LOS pressure after protein feeding (Nebel and Castell, 1972;Lipshutz et al, 1973;Roszkowski et al, 1973) have assumed rather than demonstrated an effect on circulating gastrin levels. In studies which have included serum gastrin determinations there has been a varied temporal relationship between administration of the stimulus to gastrin release, the peak gastrin response, and the change in LOS pressure (Higgs et al, 1974;McCall et al, 1975;Dent and Hansky, 1976). Furthermore, while Dent and Hansky (1976) report a rise in LOS pressure 30 minutes after the peak gastrin response to protein instillation, a similar rise was observed after intragastric instillation of a control solution of saline, this time without accompanying variation in the serum gastrin concentrations.…”
Section: -mentioning
confidence: 99%
“…In studies which have included serum gastrin determinations there has been a varied temporal relationship between administration of the stimulus to gastrin release, the peak gastrin response, and the change in LOS pressure (Higgs et al, 1974;McCall et al, 1975;Dent and Hansky, 1976). Furthermore, while Dent and Hansky (1976) report a rise in LOS pressure 30 minutes after the peak gastrin response to protein instillation, a similar rise was observed after intragastric instillation of a control solution of saline, this time without accompanying variation in the serum gastrin concentrations. They concluded that the response of the LOS to feeding may be unrelated to protein and is not related to serum gastrin levels.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee stimulates gastrin production whereas caffeine has no such effect (2). The role of gastrin, however, in the control of LOSP is disputed (6). There is good evidence that it has an important role in the physiology of the lower oesophageal sphincter (8).…”
Section: Discussionmentioning
confidence: 99%